An intersectional approach: carving out a contemporary research and practice agenda (with and for) female athletes - Steel, K. A.; O'Shea, M.; Brooks, C.; Hagstrom, A. D.; Nelson, M. (International Journal of Sports Science & Coaching, 2025)
The enhanced visibility and support for women's sports, represented by events including the 2023 FIFA Women's World Cup, and gender parity at the 2024 Paris Olympic Games (half of the competing athletes were women) are noteworthy. Despite these gains research with and for cisgender female athletes remains underdeveloped. Presently the majority of sports science research is based on male athletes. Accordingly, these studies do not address the intersectional experiences of cisgender females, contributing to significant knowledge gaps. Currently, testing and training protocols do not adequately address their efficacy among cisgender female athlete cohorts, especially in relation to fluctuating hormones, differences in body composition and biomechanics, and sociocultural influences including overall training history and movement literacies. Accordingly, this commentary identifies and critically discusses the complexities associated with this research and knowledge gap (including gender inequities, biological differences, and environmental influences), while urging a more inclusive, intersectional approach to research, training, and policy to better support cisgender female athletes` health and athletic performance.